Fat and cholesterol meat of briler chicken feed by step down protein with addition lime juice as acidifier - Hasanuddin, Sumaiya; Yunianto, Vitus Dwi; Tristiati, . (Universitas Hasanuddin, 2013)
The aim of research is to produce low fat and cholesterol in broiler meat with given lime juice (APJN) and citric acid (AS) as acidifier in step down protein feeding system, without interfering function of digestive tract of broiler. The material used were 192 birds DOC (day old chick) Hubbard strain MB 202